Exploring the Local Economic Impact of Bulbule Park Tourism from Multiple Stakeholder Perspectives - Sharma, Yamuna (Karnali Outlook: Knowledge Across Disciplines, 2026)
Bulbule Park, a popular recreational area in Birendranagar, Surkhet, has become a central hub for tourism-related economic activities in Karnali province. This study examines the local economic impacts of tourism based at Bulbule Lake using a multi-stakeholder approach to gather diverse perspectives from local park participants. A mixed-methods design was employed, combining quantitative surveys (N = 25) with qualitative in-depth interviews (N = 4), focusing on its key stakeholders: photographers, boatmen, shopkeepers, and park management staff. The study's findings show that employment generated at the park significantly fosters local economic well-being, with daily earnings generally ranging from NRs 500 to 2000. However, small businesses, especially shops, often generate higher incomes. The park has created new job opportunities, particularly for previously unemployed individuals, and has improved income levels for most workers. The study concludes that achieving lasting and sustainable economic growth depends on the full implementation of the Bulbule Master Plan and targeted investments in physical and service infrastructure. This study will contribute to strengthening policy implications for tourism planning in Karnali, in general, and in Birendranagar, in particular.